Utilização de medicamentos por crianças atendidas em creches Use of medicines by children attending nursery schools - Lucia F. Bricks; Claudio Leone (Universidade de São Paulo, 1996)
Para identificar o padrão de utilização de medicamentos em crianças, foram acompanhadas 1.382 crianças matriculadas em 15 creches municipais de São Paulo (SP)(Brasil), durante 2 meses; 512 crianças (37%) utilizaram 1.409 medicamentos (média de 50,9 medicamentos/100 crianças/ mês). Mais de 80% das crianças menores de dois anos utilizaram um ou mais medicamentos, enquanto nas outras idades esse consumo foi sempre inferior a 45%. Os fármacos mais utilizados foram os antiinfecciosos, medicamentos com ação no aparelho respiratório, e analgésicos/antitérmicos utilizados, respectivamente, por 20%, 19% e 14% das crianças estudadas. A maioria dos fármacos foi prescrita por médicos (93%), porém, mais de 65% dos antibióticos utilizados foram considerados inadequados; houve grande consumo de medicamentos de ação questionável e de fármacos não aprovados para utilização em crianças. In order to study the pattern of the use of medicines by children, 1,382 children seen at 15 of the 16 day-care centers of Pinheiros, S. Paulo city (SP)(Brasil), were followed-up for 2 months. Of these, 37% received 1,409 drugs. Average drug use was 50.9 medicines/100 children/month and the number of medicines used by each child ranged from 0 to 13. Younger children (0-2 years) received more medicines and more frequently than older children; over 80% of the younger children received one or more medicines, and more than 20% received 5 or more medicines vs . less than 45% and 5%, respectively, in the group of children aged 2-7 years. The medications most frequently employed were anti-infective, respiratory medicines and antipyretics used by, respectively, 20.1%, 19.0% and 14.0% of the children studied (usually for respiratory problems). Physicians prescribed 93% of medicines, but there were many inappropriate therapies for benign conditions, such as bronchitis and common colds. Antibiotic misure was observed (66%) including an excessive number of cloramphenicol prescriptions. Also, there were many prescriptions of doubtful value (decongestants, expectorants, vitamin and mineral supplements) and usage of as yet un approved medications for children (diclofenac, benzidamin, iodides)